Comparison of prematurity-related outcomes and complications in very low birth weight (VLBW) neonates fed with mother’s own milk versus donor milk: a comparative study - Karoobi, Majid; Azimi, Amir; Zarei, Hamed; Saboute, Maryam; Khalessi, Nasrin; Vahedi, Zahra (The Turkish Journal of Pediatrics, 2024)
Background. When mother’s own milk (MOM) is unavailable or insufficient, donor milk (DM) from a human milk bank serves as an alternative feeding option. Our study sought to investigate and compare the outcomes and complications of very low birth weight (VLBW) preterm infants who receive MOM versus DM. Methods. In this retrospective cohort study conducted between 2018 and 2022, we compared 70 VLBW preterm infants exclusively fed with DM to 70 randomly selected counterparts fed with MOM. Both groups began enteral feeding within 72 hours of birth. Various clinical outcomes were investigated during a three-month follow-up. The clinical outcomes were compared via independent t-tests, Mann-Whitney U, and Fisher’s exact test. Results. The mean gestational age of the infants who were included was 29.6 ± 1.6 weeks, 84 (60%) were males, and the average birth weight was 1217 ± 151 grams. Both groups had similar baseline characteristics. The results of the study demonstrated no statistically significant differences between the groups in terms of hospital length of stay (37±16.3 days in MOM vs 40.3±16.9 days in DM group, P= 0.17), growth rate (13±4 gram/day in MOM vs 13±4 gram/day in DM group, P=0.51), growth velocity (9.8±3.0g/kg/d in MOM vs 9.5±3.2 g/kg/d in DM group), infants with in-hospital vomiting (51 cases in MOM vs 59 cases in DM group, P=0.15),vomiting frequency (1.3±1.1 times in MOM vs 1.5±1.0 times in DM group), incidence of retinopathy of prematurity (ROP) (4 cases in MOM vs 5 cases in DM group, P>0.999) and incidence of bronchopulmonary dysplasia (BPD) (7 cases in MOM vs 6 cases in DM group, P>0.999). Conclusion. Our study findings indicate that the utilization of DM didn’t have a substantial negative impact on infants’ outcomes nor any complications in comparison with MOM.